2008
DOI: 10.1152/japplphysiol.00194.2008
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle and oral contraceptive use do not modify postexercise heat loss responses

Abstract: It is unknown whether menstrual cycle or oral contraceptive (OC) use influences nonthermal control of postexercise heat loss responses. We evaluated the effect of menstrual cycle and OC use on the activation of heat loss responses during a passive heating protocol performed pre- and postexercise. Women without OC (n = 8) underwent pre- and postexercise passive heating during the early follicular phase (FP) and midluteal phase (LP). Women with OC (n = 8) underwent testing during the active pill consumption (hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
0
6
0
5
Order By: Relevance
“…Contrary to popular belief, classic studies showed that sex had no influence on the thermoregulatory responses once VO 2max and anthropometric data were accounted for 3. Even the menstrual cycle and oral contraceptive may not affect postexercise heat loss 5…”
mentioning
confidence: 87%
“…Contrary to popular belief, classic studies showed that sex had no influence on the thermoregulatory responses once VO 2max and anthropometric data were accounted for 3. Even the menstrual cycle and oral contraceptive may not affect postexercise heat loss 5…”
mentioning
confidence: 87%
“…This could partly be explained by the fact that the amplitude of the diurnal increase in central temperature is reduced during the luteal phase (Coyne et al, 2000), potentially reducing the negative effect of the menstrual increase in central temperature during this phase. It is also important to note that neither menstrual cycle nor the use of oral contraceptives modifies post-exercise heat loss responses (Kenny et al, 2008). However, if the effect of physical training on heat acclimation is not affected by using contraceptive hormones (Armstrong et al, 2005), the increase in sweating with training may be affected by the phase of the menstrual cycle during which the training was performed (Ichinose et al, 2009).…”
Section: Menstrual Cyclementioning
confidence: 99%
“…It is used for not only contraceptive purposes, but 14% of women have used OCP for non-contraceptive purposes (Kenny et al 2008). There have been numerous studies investigating the effects of OCP on the body because the number of women using OCP has constantly increased.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies investigating the effects of OCP on the body because the number of women using OCP has constantly increased. The combined OCP contains estrogen and progesterone as synthetic steroids that prevent ovulation by inhibiting the release of follicle-stimulating hormone and luteinizing hormone from the pituitary gland in the brain (Kenny et al 2008;Krishnan and Kiley 2010). The 17-β estradiol receptors on the ACL are well established and therefore, it is of no surprise that OCP users have less ACL laxity than non-OCP users due to consistently lower levels of estradiol (Martineau et al 2004;Lee et al 2014).…”
Section: Introductionmentioning
confidence: 99%